Hemolytic Transfusion Reactions - Fatih Mehmet Azık; İkbal Ok Bozkaya; Serdar Özkasap (Güncel Pediatri)
The prevalence of fatal hemolytic transfusion reactions (HTRs) is approximately 1:200000 per unit. Acute HTRs occur during or within 24 h after administration of a blood product. Transfusion of incompatible red blood cells (RBCs), and, more rarely, of a large volume of incompatible plasma usually are the causative agents. Delayed HTRs are caused by a secondary immune response to an antigen on the donor’s RBCs. Different mechanisms lead to intra- and extravascular hemolysis, such as complete complement activation, phagocytosis of RBCs covered with C3b by macrophages after incomplete complement activation, or destruction of RBCs covered only with IgG by direct cell to cell contact with K cells. The clinical consequences of HTRs are triggered via several pathophysiological pathways. Formation of anaphylatoxins, release of cytokines causing a systemic inflammatory response syndrome, activation of the kinin system, the intrinsic clotting cascade and fibrinolysis result in hypotension, disseminated intravascular coagulation, diffuse bleeding, and disruption of microcirculation leading to renal failure and shock. In this review, the symptoms of HTR are introduced, laboratory investigations and treatment are described, and some recommendations for prevention are given. (Journal of Current Pediatrics 2011; 9: 127-32)